Spontaneous pulmonary emphysema in mice lacking all three nitric oxide synthase isoforms - Kaori Kato (Nature Portfolio, 2021)
Abstract The roles of endogenous nitric oxide (NO) derived from the entire NO synthases (NOSs) system have yet to be fully elucidated. We addressed this issue in mice in which all three NOS isoforms were deleted. Under basal conditions, the triple n/i/eNOSs−/− mice displayed significantly longer mean alveolar linear intercept length, increased alveolar destructive index, reduced lung elastic fiber content, lower lung field computed tomographic value, and greater end-expiratory lung volume as compared with wild-type (WT) mice. None of single NOS−/− or double NOSs−/− genotypes showed such features. These findings were observed in the triple n/i/eNOSs−/− mice as early as 4 weeks after birth. Cyclopaedic and quantitative comparisons of mRNA expression levels between the lungs of WT and triple n/i/eNOSs−/− mice by cap analysis of gene expression (CAGE) revealed that mRNA expression levels of three Wnt ligands and ten Wnt/β-catenin signaling components were significantly reduced in the lungs of triple n/i/eNOSs−/− mice. These results provide the first direct evidence that complete disruption of all three NOS genes results in spontaneous pulmonary emphysema in juvenile mice in vivo possibly through down-regulation of the Wnt/β-catenin signaling pathway, demonstrating a novel preventive role of the endogenous NO/NOS system in the occurrence of pulmonary emphysema.